2020
DOI: 10.1038/s41598-020-78028-4
|View full text |Cite
|
Sign up to set email alerts
|

In-situ quantification of microscopic contributions of individual cells to macroscopic wood deformation with synchrotron computed tomography

Abstract: Wood-based composites hold the promise of sustainable construction. Understanding the influence on wood cellular microstructure in the macroscopic mechanical behavior is key for engineering high-performance composites. In this work, we report a novel Individual Cell Tracking (ICT) approach for in-situ quantification of nanometer-scale deformations of individual wood cells during mechanical loading of macroscopic millimeter-scale wood samples. Softwood samples containing > 104 cells were subjected to control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…[23][24][25] More recent studies on softwood have demonstrated the disintegration of the wood structure under load (compression load). [26,27] Experiments performed with the load frame at the IBL should be considered exploratory, and consequently, the number of samples evaluated was comparably small. Nevertheless, our results show how high-resolution imaging of load sequences and the subsequent localization of strain can be applied to reveal functional relationships with sample morphology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25] More recent studies on softwood have demonstrated the disintegration of the wood structure under load (compression load). [26,27] Experiments performed with the load frame at the IBL should be considered exploratory, and consequently, the number of samples evaluated was comparably small. Nevertheless, our results show how high-resolution imaging of load sequences and the subsequent localization of strain can be applied to reveal functional relationships with sample morphology.…”
Section: Discussionmentioning
confidence: 99%
“…[ 23–25 ] More recent studies on softwood have demonstrated the disintegration of the wood structure under load (compression load). [ 26,27 ]…”
Section: Discussionmentioning
confidence: 99%
“…In situ micro-CT studies are very powerful for investigating the local deformation behavior of tissues and cells upon external loading of bulk samples. To study wood structure and mechanics, sophisticated testing devices were built and cell deformations were studied with high resolution [30][31][32][33]. Figure 6 shows micro-CT images of bamboo slivers loaded in a simple testing setup, which were analyzed at the three different levels of span length reduction to measure the area change of PCs during the bending deflection.…”
Section: Deformation Of Bamboo Cells During Bending Displacementmentioning
confidence: 99%
“…For the same reason, water uptake occurs preferentially only in latewood in the case of heartwood 48 . Synchrotron facilities, which are capable of combining very high resolution with short acquisition times, have been successfully applied to the study of lignocellulosic products 58 – 60 .…”
Section: Introductionmentioning
confidence: 99%